The Transformation of Academic Culture in Islamic Boarding Schools through Green Islam-Based Education - Saepulmilah, Ceceng; Saepullah, Asep; Rakhmat, Anwar Taufik (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study examines the transformation of academic culture at Pondok Pesantren Hamalatul Quran Manonjaya through the lens of Green Islam. The research focuses on practices of cleanliness, agriculture, leadership, and the role of ustadz/ustadzah (teachers) in fostering ecological awareness grounded in Islamic values. A qualitative ethnographic method was employed, involving 15 respondents comprising school leaders, teachers, administrators, and senior students. Data were collected through interviews, observations, and documentation, and subsequently analyzed thematically. The findings reveal that cleanliness is perceived as an integral part of faith; agricultural and greening activities function as ecological learning media; the pesantren’s leadership demonstrates a visionary approach with environmentally conscious policies; teachers integrate Islamic teachings into daily practices; while student discipline is maintained through humane and educational sanctions. This research concludes that Hamalatul Quran has successfully developed an eco-pesantren model grounded in Green Islam harmoniously integrating religious tradition, modernity, and ecological awareness in a sustainable manner.